Pengaruh Kinerja dan Profesionalitas Guru Pendidikan Agama Islam dan Budi Pekerti Terhadap Penerapan Kurikulum Merdeka di SMP Kabupaten Kaur Provinsi Bengkulu - Siratjudin Siratjudin; nurlaili nurlaili; Desy Eka Citra Dewi (UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to (1) analyze the magnitude of the influence of the performance of PAI BP teachers on the implementation of the independent curriculum in SMP Kaur Regency, Bengkulu Province (2) analyze the magnitude of the influence of the professionalism of PAI BP teachers on the implementation of the independent curriculum in SMP Kaur Regency, Bengkulu Province (3) analyze the magnitude of the influence of the performance and professionalism of PAI BP teachers on the implementation of the independent curriculum in SMP Kaur Regency, Bengkulu Province. The type of research used in this study is quantitative research, the research instrument used in this study is a questionnaire, the data analysis techniques used are descriptive statistics, basic assumption tests, classical assumption tests, and hypothesis tests using simple linear regression and multiple linear regression, t test and f test. the results of this study: (1). there is an influence of the performance of PAI and Budi Pekerti teachers on the implementation of the independent curriculum in SMP Kaur Regency, Bengkulu Province as shown in the calculated t (2,053) > t table (5% = 1.70) and a significance level of 0.046 < 0.05. (2). there is an influence of the professionalism of PAI Budi Pekerti teachers on the implementation of the independent curriculum at SMP Kaur Regency, Bengkulu Province, which is shown in the t count (2.862) > t table (5% = 1.70) and a significance level of 0.007 < 0.05. (3). there is an influence of the performance and professionalism of PAI Budi Pekerti teachers on the implementation of the independent curriculum at SMP Kaur Regency, Bengkulu Province, which is shown in the t count (3.875) > t table (5% = 2.85) and a significance level of 0.032 < 0.05.